Disparity And Volatility of Horticultural Prices In Indonesia Before and Pandemic Period (2019 and 2020) - Bhinadi, Ardito (AIBPM Publisher, 2023)
Disparity, volatility, and asymmetry of horticultural agricultural commodity prices are important to study during the COVID-19 pandemic. The increase in horticultural prices can cause inflation and reduce the level of real welfare. The disparity in horticultural prices will encourage the flow of goods from low-priced to high-priced areas. The volatility of food prices during the COVID-19 pandemic will add economic pressure to the community. This study aims to analyze the disparity and volatility of horticultural prices and the transmission of food prices from upstream to downstream before and during the 2019-2020 pandemic. The analytical tools used are the average, price difference, coefficient of variation, and error correction model. The results show a disparity in food prices between provinces in Indonesia. Price disparities increase during the pandemic. Price volatility during the pandemic for horticultural commodities is higher than before the pandemic. Changes in horticulture prices at the upstream level significantly affect price changes at the downstream level